Revisit of an Improved Wilker Type Inequality - Rupali Shinde; Christophe Chesneau; Nitin Darkunde; Sanjay Ghodechor; Aditya Lagad (Pan-American Journal of Mathematics, 2023)
In this article, we revisit an improved Wilker type inequality established in 2020. We fill some gaps in the existing proof and propose an alternative proof using the same mathematical ingredients. All the details are given for checking purposes.